Overview of Academic Procrastination of Students Working on Thesis at Muhammadiyah University of Sidoarjo - Satrio Agung Pranoto; Ghozali Rusyid Affandi (Journal of Islamic and Muhammadiyah Studies, 2023)
This research is motivated by the delay of students in working on the thesis. The purpose of this study is to find out and provide an explanation of the description of the academic procrastination of students who are working on their thesis at the Muhammadiyah University of Sidoarjo. This research method is descriptive quantitative with the subject of students who are working on a thesis totaling 292 students. Determination of subjects using proportionate stratified random sampling technique is a sampling technique used when the population has members or elements that are not homogeneous and stratified proportionally. The variable in this study is academic procrastination. The data collection in this study used a psychological preparation scale, namely the Likert scale for the academic procrastination variable made by the researcher. Analysis of the data in this study using the help of Microsoft Excel. The results of data analysis showed that male students had higher procrastination than female students with an average score of 57.18, while female students had an average of 55.59. The results of the study when viewed from the Faculty show that the SAINTEK faculty has the highest level of academic procrastination among other faculties. The results of the study based on morning and evening classes showed that the evening class (56.6) had higher academic procrastination than the morning class (55.5).